Younger Supervisors' Perceptions of Intergenerational Communication in the Sri Lankan Workplace. (March 2023) - Jeevaratnam, Grace Ashna; Jones, Elizabeth
Workplaces are increasingly seeing younger supervisors supervise older subordinates, reversing traditional norms. Using Communication Accommodation Theory, we investigated younger supervisors' perceptions of communication with same-aged and older subordinates in Sri Lanka. Eighty young supervisors rated four vignettes describing formal and informal interactions with same-aged and older subordinates. Participants rated older subordinates' communication as less accommodative and more nonaccommodative than same-aged subordinates, particularly in formal interactions. They rated their own communication as more polite and respectful with older than same-aged subordinates.